2023
DOI: 10.1101/2023.04.25.538305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superior Efficacy of Combination Antibiotic Therapy versus Monotherapy in a Mouse Model of Lyme Disease

Abstract: Lyme disease (LD) results from the most prevalent tick-borne infection in North America, with over 476,000 estimated cases annually. The disease is caused by Borrelia burgdorferi (Bb) which transmits through the bite of Ixodid ticks. Most cases treated soon after infection are resolved by a short course of oral antibiotics. However, 10-20% of patients experience chronic symptoms because of delayed or incomplete treatment, a condition called Post-Treatment Lyme Disease (PTLD). Some Bb persists in PTLD patients … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The study by Sapi et al confirmed the culture findings found by Feng et al at Johns Hopkins University on the superior efficacy of dapsone against Borrelia persisters using multiple antibiotic combinations [ 108 ]. To date, there has been one animal study by Embers et al (pre-print) proving dapsone’s efficacy in Lyme disease in a mouse model [ 237 ], which confirmed the superior efficacy of combination antibiotic therapy vs. monotherapy in the treatment of borreliosis. The findings of that study were that “none of the monotherapies eradicated persistent Bb; however, 4 dual combinations, including dapsone + rifampicin, dapsone + clofazimine, and 3 triple combinations (including dapsone + rifampicin + clofazimine), eradicated persistent Bb infections” [ 237 ].…”
Section: Discussionmentioning
confidence: 95%
“…The study by Sapi et al confirmed the culture findings found by Feng et al at Johns Hopkins University on the superior efficacy of dapsone against Borrelia persisters using multiple antibiotic combinations [ 108 ]. To date, there has been one animal study by Embers et al (pre-print) proving dapsone’s efficacy in Lyme disease in a mouse model [ 237 ], which confirmed the superior efficacy of combination antibiotic therapy vs. monotherapy in the treatment of borreliosis. The findings of that study were that “none of the monotherapies eradicated persistent Bb; however, 4 dual combinations, including dapsone + rifampicin, dapsone + clofazimine, and 3 triple combinations (including dapsone + rifampicin + clofazimine), eradicated persistent Bb infections” [ 237 ].…”
Section: Discussionmentioning
confidence: 95%